Blood–brain and retinal barriers show dissimilar ABC transporter impacts and concealed effect of P‐glycoprotein on a novel verapamil influx carrier. (15th January 2016) - Chapy, Hélène; Saubaméa, Bruno; Tournier, Nicolas; Bourasset, Fanchon; Behar‐Cohen, Francine; Declèves, Xavier; Scherrmann, Jean‐Michel; Cisternino, Salvatore
Abstract : Background and Purpose: The respective impact and interplay between ABC (P‐glycoprotein/P‐gp/Abcb1a, BCRP/ABCG2, MRP/ABCC) and SLC transporter functions at the blood–brain barrier (BBB) and blood–retinal barriers (BRB) are incompletely understood. Experimental Approach: We measured the initial cerebral and retinal distribution of selected ABC substrates by in situ carotid perfusion using P‐gp/Bcrp knockout mice and chemical ABC/SLC modulation strategies. P‐gp, Bcrp, Mrp1 and Mrp4 were studied by confocal retina imaging. Key Results: Chemical or physical disruption of P‐gp increased [ 3 H]‐verapamil transport by 10‐fold at the BBB and 1.5‐fold at the BRB. [ 3 H]‐Verapamil transport involved influx‐mediated by an organic cation clonidine‐sensitive/diphenhydramine‐sensitive proton antiporter at both barriers; this effect was unmasked when P‐gp was partially or fully inhibited/disrupted at the BBB. Studies of [ 3 H]‐mitoxantrone and [ 3 H]‐zidovudine transport suggested, respectively, that Bcrp efflux was less involved at the BRB than BBB, whereas Mrps were significantly and similarly involved at both barriers. Confocal imaging showed that P‐gp and Bcrp were expressed in intra‐retinal vessels (inner BRB/iBRB) but absent from the blood/basal membrane of cells of the retinal pigment epithelium (outer BRB/oBRB/RPE) where, in contrast, Mrp1 and Mrp4 were localized. Conclusions and Implications: P‐gp, Bcrp, Mrp1 and Mrp4 are differentially expressed at the outer and inner BRB, resulting in an altered ability to limit substrate distribution at the retina as compared with the BBB. [ 3 H]‐Verapamil distribution is not P‐gp‐specific and involves a proton antiporter at both the BBB and BRB. However, this transport is concealed by P‐gp at the BBB, but not at the BRB, where P‐gp activity is reduced.